Post-exercise branched chain amino acid supplementation does not affect recovery markers following three consecutive high intensity resistance training bouts compared to carbohydrate supplementation. Issue 1 (December 2016) - Kephart, Wesley; Mumford, Petey; McCloskey, Anna; Holland, A.; Shake, Joshua; Mobley, C.; Jagodinsky, Adam; Weimar, Wendi; Oliver, Gretchen; Young, Kaelin; Moon, Jordan; Roberts, Michael
Abstract Background Amino acid supplementation has been shown to potentially reduced exercise-induced muscle soreness. Thus, the purpose of this study was to examine if branched chain amino acid and carbohydrate (BCAACHO) versus carbohydrate-only sports drink (CHO) supplementation attenuated markers of muscle damage while preserving performance markers following 3 days of intense weight training. Methods Healthy resistance-trained males (n  = 30) performed preliminary testing (T1) whereby they: 1) donated a baseline blood draw, 2) performed knee extensor dynamometry to obtain peak quadriceps isometric and isokinetic torque as well as electromyography (EMG) activity at 60°/s and 120°/s, and 3) performed a one repetition maximum (1RM) barbell back squat. The following week participants performed 10 sets x 5 repetitions at 80 % of their 1RM barbell back squat for 3 consecutive days and 48 h following the third lifting bout participants returned for (T2) testing whereby they repeated the T1 battery. Immediately following and 24 h after the three lifting bouts, participants were randomly assigned to consume one of two commercial products in 600 mL of tap water: 1) BCAAs and CHO (3 g/d L-leucine, 1 g/d L-isoleucine and 2 g/d L-valine with 2 g of CHO;n  = 15), or 2) 42 g of CHO only (n  = 15). Additionally, venous blood was drawn 24 h following the first and second lifting bouts and 48 h following the third bout to assess serum myoglobin concentrations, and a visual analog scale was utilized prior, during, and after the 3-d protocol to measure subjective perceptions of muscular soreness. Results There were similar decrements in 1RM squat strength and isokinetic peak torque measures in the BCAA-CHO and CHO groups. Serum myoglobin concentrations (p  = 0.027) and perceived muscle soreness (p  < 0.001) increased over the intervention regardless of supplementation. A group*time interaction was observed for monocyte percentages (p  = 0.01) whereby BCAA-CHO supplementation attenuated increases in this variable over the duration of the protocol compared to CHO supplementation. Conclusion BCAA-CHO supplementation did not reduce decrements in lower body strength or improve select markers of muscle damage/soreness compared to CHO supplementation over three consecutive days of intense lower-body training.